First, use these two rules of exponents to eliminate the outer exponent:
#a = a^color(red)(1)# and #(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(x^color(red)(1)y^color(red)(5)z^color(red)(-2))^color(blue)(-1) = x^(color(red)(1) xx color(blue)(-1))y^(color(red)(5) xx color(blue)(-1))z^(color(red)(-2) xx color(blue)(-1)) = x^-1y^-5z^2#
Next, we can use this rule of exponents to eliminate the negative exponents:
#x^color(red)(a) = 1/x^color(red)(-a)#
#x^color(red)(-1)y^color(red)(-5)z^2 = z^2/(x^color(red)(- -1)y^color(red)(- -5)) = z^2/(x^color(red)(1)y^color(red)(5))#
Now, use this rule of exponents to complete the simplification:
#a^color(red)(1) = a#
#z^2/(x^color(red)(1)y^5) = z^2/(xy^5)#